The Influence of Using Interactive Food Chain Diorama Learning Media on Students' Learning Interests - Alfian Farhanto; Dya Ayu Agustiana Putri; Eka Yuliana Sari (Yayasan Dinamika Ilmu Banyuwangi, 2025)
Natural Science is introduced and used universally, starting from elementary school to university level. level. However, IPA is perceived as one of the most daunting and difficult subjects. and quite difficult. Many students are not interested in learning Science. Based on this, learning media that can attract students' interest to learn Science is needed. to learn natural science. The media that can be used is interactive Diorama. Natural science, this study aims to examine the effect of using learning media in the form of learning media in the form of Diorama on the learning Interest of Five grade students of SDN 1 Keboireng. This research method with a quasi-experiment design, involving 52 students who were divided into two classes (experiments and control). divided into two classes (experiments and control). Researchers used 3 types of data analysis data normality test, data homogeneity test, Independent Sample T-Test test using JAMOVI 2.3.2 software for windows. From the results of research and discussion on the Independent Sample T-test test, it can be seen that the P value isobtained 0.152 Because the p value> 0.05 then Hoaccepted so that it can have less / lower than (<0.05). The p value <0.05 then Ho is rejected so it can be concluded that Ha is accepted. There is no influence on students' learning Interest elementary school experimental class with the control class at the time of the pre-test, while at the time of the post-test in the control and experimentalclasses, the p-value <0.001 was concluded. when the post-test was carried out in the control and experimental classes, the p-value <0.001 was concluded that, there is a significant influence on learning Interest between students who take part in learning using the learning media of the Interactive Diorama with students who do not use the learning media.